KOMBINASI TRAY AERATOR DAN FILTRASI UNTUK MENURUNKAN KADAR BESI (FE) DAN MANGAN (MN) PADA AIR SUMUR - Al Kholif, Muhammad; Sugito, Sugito; Pungut, Pungut; Sutrisno, Joko (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 1 (2020)DO - 10.24843/EJES.2020.v14.i01.p03, 2020)
The problem that is often found in water well is the high content of iron (Fe) and manganese (Mn). This study aims to decrase the content of Fe and Mn in water well with aeration and filtration systems. Aeration used is a multilevel tray aerator by using a tray within 50 cm, while the filtration media used are activated carbon and zeolite sand with a height of 70 cm each. The results showed that the aeration process with tray aerator was able to reduce Fe levels up to 98.34% and Mn reached 97.40%. In the filtration process with activated carbon can reduce Fe levels by 98.48% and Mn by 98.25%. In the filtration process with zeolite sand media can reduce Fe levels by 98.43% and Mn by 97.44%.